Results of using The early Childhood Education Curriculum of Schools Under The Ubon Ratchathani Primary Educational Service Area Office 3: Early Childhood Educational institution Curriculum, Results of using The Curriculum - Thanopajai, Sirithai (Ubon Ratchathani Journal of Research and Evaluation, 2024)
This research aims to 1) study the results of using the early childhood education curriculum of schools under the Ubon Ratchathani Primary Educational Service Area Office, Area 3, 2) to evaluate early childhood development, and 3) survey parents' satisfaction with Continue the curriculum for early childhood education institutions. The target group was the executive committee of the early childhood education institution curriculum, numbering 497 people, obtained through purposive selection. A total of 8,127 early childhood children were used as the target group. and parents of 297 early childhood children, which were obtained by calculating from ready-made tables by Krejcie and Morgan. The research tools included an opinion questionnaire and a satisfaction assessment form. Statistics used in research include percentages, averages, and standard deviations. The research findings were as follows: Results of using the early childhood education curriculum of schools under the Ubon Ratchathani Primary Educational Service Area Office, Area 3, including all aspects. The practice level was 100% with the highest average level ( =4.72). The results of the early childhood development assessment found that early childhood children received preparation in all 4 areas: physical, emotional, and mental. Social and intellectual aspects at a high level When classified into each aspect of development, it was found that the aspect with the highest average was the social aspect at 94.06 percent, the emotional aspect at 93.92 percent, the physical aspect at 88.82 percent, and the intellectual aspect at 87.66 percent. Satisfaction of parents of early childhood children with the use of the early childhood education curriculum. It was found that overall they were satisfied. It is at the highest level with an average ( =4.70) and when considering each aspect, it is found that the highest level of satisfaction is in the quality of children ( =4.74), followed by the promotion aspect. Support early childhood education ( = 4.72 ) and have the lowest level of satisfaction in terms of teachers and learning experiences ( = 4.64 ).